The impact of international television : a paradigm shift - Elasmar, Michael G. (LEA's communication series., 2003)
For several decades, cultural imperialism has been the dominant paradigm for conceptualizing, labeling, predicting, and explaining the effects of international television. It has been used as an unchallenged premise for numerous essays on the topic of imported television influence, despite the fact that the assumption of strong cultural influence is not necessarily reflected in the body of research that exists within this field of study. In The Impact of International Television: A Paradigm Shift, editor Michael G. Elasmar and his contributors challenge the dominant paradigm of cultural.